A composite photocatalytic material for regenerating a manganese-based catalyst in situ, a preparation method and applications thereof
Patent Information
- Application Number
- CN202610895877.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-22
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]另一方面,现有技术中也有MnO2改性TiO2复合光催化剂用于甲醛等有机污染物的吸附与光降解,并通过紫外光对该光催化剂自身进行再生的技术方案,但该类技术的目标对象主要是室内VOC去除,其被再生的是光催化剂本身,而非失活锰基主催化剂,且其技术手段和实际要解决的技术问题均不同于锰基催化剂在含硫含水工况下的原位恢复需求
[0027] 1. This invention provides a composite photocatalytic material for in-situ regeneration of manganese-based catalysts, its preparation method, and its application. By synergistically combining a manganese-cerium composite oxide host phase, a phosphorus/sulfur co-doped carbon-nitrogen photosensitive phase, and KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters, a multifunctional system possessing redox activity, visible light responsiveness, and surface acidity regulation capability is constructed. Specifically, the manganese-cerium composite oxide host phase enhances the oxygen migration capacity and stability of high-valence manganese species; the phosphorus/sulfur co-doped carbon-nitrogen photosensitive phase broadens the visible light absorption range and improves the photogenerated carrier separation efficiency; and the KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters further enhance interfacial electron transfer and surface acidity site density. Therefore, the composite photocatalytic material of this invention achieves a high specific surface area, abundant surface oxygen vacancies, and superior initial photocatalytic activity.
Abstract
Description
Technical Field
[0001] This invention relates to the field of photocatalytic materials technology, specifically to a composite photocatalytic material for in-situ regeneration of manganese-based catalysts, its preparation method, and its application. Background Technology
[0002] Manganese-based catalysts are widely considered important candidate materials for low-temperature NH3-SCR denitrification, VOCs catalytic oxidation, and various gas purification reactions due to their high activity at low temperatures, excellent redox performance, and relatively low preparation cost. However, in practical applications, components such as SO2, H2O, NH3, and NOx in flue gas tend to form ammonium bisulfate, ammonium sulfate, nitrate, and metal sulfate coatings on the surface of manganese-based catalysts, or generate difficult-to-remove organic deposits. This results in active site shielding, hindered Mn valence state cycling, decreased surface acidity, and weakened oxygen migration capacity, ultimately leading to a significant decline in catalyst activity.
[0003] Existing methods for regenerating manganese-based catalysts mostly employ offline processes such as water washing, acid washing, activation solution impregnation, and thermal calcination. While these methods can restore catalytic activity to some extent, they typically suffer from drawbacks such as requiring equipment disassembly, high regeneration energy consumption, long process downtime, easy generation of secondary waste liquid, and loss of active components. These methods fail to meet the practical needs of low-cost, convenient in-situ regeneration under continuous operating conditions. Therefore, achieving efficient regeneration of manganese-based catalysts under relatively mild conditions remains a pressing technical problem to be solved in this field.
[0004] On the other hand, existing technologies also include MnO2-modified TiO2 composite photocatalysts for the adsorption and photodegradation of organic pollutants such as formaldehyde, and regeneration of the photocatalyst itself using ultraviolet light. However, this type of technology primarily targets indoor VOC removal, and what is being regenerated is the photocatalyst itself, not the deactivated manganese-based main catalyst. Furthermore, its technical methods and the actual technical problems it addresses differ from the in-situ recovery requirements of manganese-based catalysts under sulfur- and water-containing conditions. Therefore, developing a composite photocatalytic material that can promote the removal of deposits on the surface of deactivated manganese-based catalysts and the recovery of high-valence manganese active sites under visible light and oxygen-containing atmospheres is of great significance for extending catalyst service life, reducing regeneration costs, and improving recycling performance. Summary of the Invention
[0005] To address the shortcomings of the existing technologies, this invention provides a composite photocatalytic material for in-situ regeneration of manganese-based catalysts, its preparation method, and its application.
[0006] While existing porous manganese-based materials exhibit good low-temperature redox activity, they are prone to forming deposits such as sulfates, ammonium bisulfate, ammonium sulfate, and nitrates under conditions containing SO2 and H2O. This leads to the shading of active sites, pore blockage, reduction of surface reactive oxygen species, and a decrease in the proportion of high-valence manganese species. At the same time, single manganese-based materials have low visible light utilization and rapid photogenerated electron-hole recombination, making it difficult to simultaneously achieve deposit removal and active site recovery, thus limiting their regeneration capacity.
[0007] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows:
[0008] A composite photocatalytic material for in-situ regeneration of manganese-based catalysts, the composite photocatalytic material for in-situ regeneration of manganese-based catalysts comprising a manganese-cerium composite oxide host phase, a phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase, and a KEGIN-structured phosphotungsten heteropolyacid nanocluster.
[0009] The manganese-cerium composite oxide host phase is a porous structure enriched with oxygen vacancies. The phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase is loaded on the surface of the manganese-cerium composite oxide host phase. The KEGIN structure phosphotungsten heteropolyacid nanoclusters are fixed on the surface of the manganese-cerium composite oxide host phase and form an interface contact with the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase.
[0010] The composite photocatalytic material used for in-situ regeneration of manganese-based catalysts can promote the removal of deposits on the surface of deactivated manganese-based catalysts and promote the recovery of high-valence active sites of manganese under visible light irradiation and oxygen-containing atmosphere.
[0011] This invention first introduces cerium doping into a porous manganese-based substrate because Ce... 4+ / Ce 3+ The reversible redox cycle and its strong oxygen storage / release capacity are beneficial to improving the oxygen vacancy content and lattice oxygen migration ability on the material surface. It also promotes charge transfer between Mn and Ce through Ce-O-Mn interaction, thereby stabilizing multivalent manganese species and slowing down the deactivation process caused by SO2 / H2O. At the same time, the introduction of cerium can also improve the tolerance to sulfur-containing deposits, making species such as ammonium bisulfate formed on the surface easier to be activated and subsequently decomposed.
[0012] This invention further incorporates a phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase. While carbon-nitrogen materials inherently possess visible light responsiveness, unmodified carbon-nitrogen materials still suffer from limited light absorption range and insufficient carrier separation efficiency. Through phosphorus and sulfur co-doping, their electronic structure can be tuned, broadening the visible light absorption range and improving surface defect sites and electron migration efficiency. Furthermore, phosphorus / sulfur co-doped carbon-nitrogen quantum dots and phosphorus / sulfur co-doped g-C3N4 nanosheets are synergistically constructed. On the one hand, quantum dots promote rapid electron extraction; on the other hand, two-dimensional nanosheets provide a larger specific surface area and transport channels, thereby significantly enhancing visible light excitation and reactive oxygen species generation capabilities.
[0013] Preferably, the manganese-cerium composite oxide host phase accounts for 70-90 wt% of the total mass of the composite photocatalytic material, the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase accounts for 3-15 wt%, and the KEGIN-structured phosphotungsten heteropolyacid nanoclusters account for 2-12 wt%.
[0014] Furthermore, this invention introduces KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters. This component can promote the adsorption, activation, and decomposition of deposits such as ammonium bisulfate, sulfate, and nitrate; simultaneously, it also possesses excellent electron acceptor properties, serving as an interfacial electron transport unit to promote the directional migration of photogenerated electrons and enhance O2 activation. Thus, it not only increases the density of acidic sites on the material surface but also strengthens the interfacial synergy between the manganese-cerium host phase and the doped carbon photosensitive phase.
[0015] Preferably, the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase is one or both of phosphorus / sulfur co-doped carbon-nitrogen quantum dots and phosphorus / sulfur co-doped graphitic carbon nitride nanosheets; the average particle size of the carbon-nitrogen quantum dots is 2-10 nm, and the thickness of the graphitic carbon nitride nanosheets is 1-20 nm.
[0016] Preferably, the Kägerin-structured phosphotungsten heteropolyacid nanoclusters are H3PW. 12 O 40 NH4H2PW 12 O 40 K3PW 12 O 40 One or more of them.
[0017] Preferably, the specific surface area of the composite photocatalytic material used for in-situ regeneration of manganese-based catalysts is 50-250 m². 2 / g, with a relative content of 5-30% of surface oxygen vacancies.
[0018] The method for preparing the composite photocatalytic material for in-situ regeneration of manganese-based catalysts includes the following steps:
[0019] (1) Manganese and cerium sources were used to prepare a manganese-cerium composite oxide precursor by hydrothermal method and then heat-treated to obtain a porous manganese-cerium composite oxide host phase;
[0020] (2) Introduce a precursor containing P, S and N onto the surface of the main phase and form a phosphorus / sulfur co-doped carbon and nitrogen photosensitive phase by thermal polymerization or hydrothermal treatment;
[0021] (3) Phosphotungstic acid or its ammonium salt or alkali metal salt is introduced into the surface of the main phase of the manganese cerium composite oxide or the surface of the composite intermediate loaded with phosphorus / sulfur co-doped carbon and nitrogen photosensitive phase and fixed to obtain the composite photocatalytic material for in-situ regeneration of manganese-based catalyst.
[0022] Preferably, the manganese source in step (1) is one or more of manganese nitrate, manganese acetate, and manganese chloride, and the cerium source is one or more of cerium nitrate, cerium acetate, and cerium chloride; the heat treatment temperature is 300-500℃ and the time is 1-5h.
[0023] Preferably, the precursor containing P, S, and N in step (2) includes one or more of melamine, urea, thiourea, trithiocyanate, ammonium dihydrogen phosphate, and phytic acid; the thermal polymerization temperature is 350-550℃ and the time is 0.5-4h; or phosphorus / sulfur co-doped carbon-nitrogen quantum dots are prepared by a hydrothermal method at 160-220℃.
[0024] Preferably, the fixed processing temperature in step (3) is 120-300℃ and the time is 0.5-3h.
[0025] The application of the composite photocatalytic material in recyclable manganese-based composite photocatalytic materials.
[0026] The beneficial effects of this invention are:
[0027] 1. This invention provides a composite photocatalytic material for in-situ regeneration of manganese-based catalysts, its preparation method, and its application. By synergistically combining a manganese-cerium composite oxide host phase, a phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase, and KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters, a multifunctional system possessing redox activity, visible light responsiveness, and surface acidity regulation capability is constructed. Specifically, the manganese-cerium composite oxide host phase enhances the oxygen migration capacity and stability of high-valence manganese species; the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase broadens the visible light absorption range and improves the photogenerated carrier separation efficiency; and the KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters further enhance interfacial electron transfer and surface acidity site density. Therefore, the composite photocatalytic material of this invention achieves a high specific surface area, abundant surface oxygen vacancies, and superior initial photocatalytic activity.
[0028] 2. The composite photocatalytic material of this invention can effectively improve the problem that ordinary manganese-based materials are prone to sulfate, ammonium bisulfate, ammonium sulfate, and nitrate deposition under SO2 and H2O conditions, which leads to active site masking, a decrease in the proportion of high-valent manganese species, and a decline in catalytic efficiency. Under visible light irradiation and an oxygen-containing atmosphere, the material of this invention can promote the removal of deposits on the surface of the deactivated material through a synergistic process of light absorption—electron separation—oxygen activation—deposit decomposition—high-valent manganese recovery, and accelerate the recovery of the redox cycle between Mn and Ce, thereby significantly improving the material's resistance to deactivation, in-situ regeneration ability, and photocatalytic efficiency after regeneration.
[0029] 3. The composite photocatalytic material provided by this invention can be regenerated in situ under relatively mild conditions after deactivation, without the need for complex high-temperature calcination, acid washing, or disassembly. It has the advantages of mild regeneration conditions, simple process, and good reusability. Compared with existing ordinary manganese-based materials or simple composite photosensitive materials, this invention, through multi-component synergistic design, takes into account higher activity, stronger resistance to deactivation, and good recycling performance, making it more suitable for widespread application as a recyclable manganese-based composite photocatalytic material. Detailed Implementation
[0030] The invention will now be described in further detail with reference to specific embodiments, but it should not be construed as limiting the scope of the invention to the following embodiments.
[0031] The raw materials described in this application are partially described; all other raw materials not described are commercially available.
[0032] Example 1
[0033] A method for preparing a composite photocatalytic material for in-situ regeneration of manganese-based catalysts includes the following steps:
[0034] (1) Preparation of porous manganese-cerium composite oxide host phase: Weigh 8.0 g of manganese nitrate tetrahydrate and 1.6 g of cerium nitrate hexahydrate, dissolve them in 120 mL of water, add 9.0 g of urea and 3.0 g of glucose, stir at room temperature for 30 min, and then hydrothermally react at 160 °C for 10 h. After the reaction is completed, centrifuge to collect the precipitate, wash until neutral, dry, and then calcine at 400 °C for 2 h in air atmosphere to obtain porous manganese-cerium composite oxide host phase;
[0035] (2) Preparation and loading of phosphorus / sulfur co-doped carbon and nitrogen quantum dots: 2.0 g of citric acid, 2.5 g of thiourea and 1.0 g of ammonium dihydrogen phosphate were weighed and dissolved in 60 mL of water. After stirring evenly, the mixture was subjected to hydrothermal reaction at 180 °C for 8 h. After cooling, a dispersion of phosphorus / sulfur co-doped carbon and nitrogen quantum dots was obtained. 5.0 g of the above porous manganese cerium composite oxide host phase was added to the dispersion. The mixture was ultrasonicated at 200 W and 60 kHz for 30 min. Then, it was stirred at 400 rpm for 4 h. After filtration, washing and drying, the mixture was treated at 200 °C for 1 h to obtain a manganese-based composite intermediate loaded with phosphorus / sulfur co-doped carbon and nitrogen quantum dots.
[0036] (3) Introduction of Kegerin-structured phosphotungstic heteropolyacid nanoclusters: 0.5g of phosphotungstic acid H3PW 12 O 40 Dissolve in 40 mL of 40 wt% ethanol-water mixture, add the intermediate obtained in step (2), stir at room temperature for 6 h, remove solvent by rotary evaporation, fix at 180 °C for 1.5 h, and obtain composite photocatalytic material for in-situ regeneration of manganese-based catalyst.
[0037] Example 2
[0038] A method for preparing a composite photocatalytic material for in-situ regeneration of manganese-based catalysts includes the following steps:
[0039] (1) Prepare the porous manganese-cerium composite oxide host phase according to step (1) of Example 1;
[0040] (2) Weigh 6.0g of melamine, 3.0g of thiourea and 1.2g of ammonium dihydrogen phosphate, mix them evenly and place them in a covered crucible, heat them to 520℃ at 3℃ / min, keep them at 520℃ for 2h, cool them to room temperature, grind them to obtain phosphorus / sulfur co-doped g-C3N4 powder; weigh 1.0g of the above phosphorus / sulfur co-doped g-C3N4 powder and add it to 300mL of 20wt% ethanol-water mixture, stir it at room temperature for 30min; place it in an ice-water bath and sonicate it at an ultrasonic power of 400W and an ultrasonic frequency of 80kHz for 1h; centrifuge it and take the supernatant to obtain phosphorus / sulfur co-doped g-C3N4 nanosheet dispersion; add 5.0g of the main phase obtained in step (1) to the nanosheet dispersion obtained in step (2), stir it at room temperature for 5h, remove the solvent under reduced pressure, dry it to obtain manganese cerium composite oxide intermediate loaded with phosphorus / sulfur co-doped g-C3N4 nanosheets;
[0041] (3) Separately add 0.5g H3PW 12 O 40 Dissolve in 40 mL of 40 wt% ethanol-water mixture, add the intermediate obtained in step (2), stir at room temperature for 6 h, remove solvent by rotary evaporation, fix at 180 °C for 1.5 h, and obtain composite photocatalytic material for in-situ regeneration of manganese-based catalyst.
[0042] Example 3
[0043] A method for preparing a composite photocatalytic material for in-situ regeneration of manganese-based catalysts includes the following steps:
[0044] (1) Prepare the porous manganese-cerium composite oxide host phase according to step (1) of Example 1;
[0045] (2) Prepare a phosphorus / sulfur co-doped carbon-nitrogen quantum dot dispersion according to step (2) of Example 1;
[0046] (3) Prepare a phosphorus / sulfur co-doped g-C3N4 nanosheet dispersion according to step (2) of Example 2;
[0047] (4) 5.0 g of the manganese-cerium composite oxide host phase was simultaneously dispersed in carbon-nitrogen quantum dot dispersion and g-C3N4 nanosheet dispersion, so that the total loading of the dual photosensitive phase accounted for 10 wt% of the total mass of the final material. The mixture was stirred at room temperature for 5 h, the solvent was removed by vacuum evaporation, and the mixture was dried to obtain a manganese-based composite intermediate loaded with phosphorus / sulfur co-doped carbon-nitrogen material; then 0.5 g of H3PW was added. 12 O 40 Dissolved in 40 mL of a 40 wt% ethanol-water mixture, stirred at room temperature for 6 h, solvent removed by rotary evaporation, and kept at 180 °C for 1.5 h, a composite photocatalytic material for in-situ regeneration of manganese-based catalysts was obtained.
[0048] The carbon-nitrogen quantum dot dispersion was concentrated under reduced pressure and adjusted to a mass concentration of 10 mg / mL. The phosphorus / sulfur co-doped g-C3N4 nanosheet dispersion was concentrated under reduced pressure and adjusted to a mass concentration of 10 mg / mL. The mass ratio of phosphorus / sulfur co-doped carbon-nitrogen quantum dots to phosphorus / sulfur co-doped g-C3N4 nanosheets was 3:7. 18.3 mL of the phosphorus / sulfur co-doped carbon-nitrogen quantum dot dispersion and 42.8 mL of the phosphorus / sulfur co-doped g-C3N4 nanosheet dispersion were added to the manganese-cerium composite oxide bulk phase, respectively.
[0049] Example 4
[0050] It is basically the same as Example 3, except that the H3PW in step (4) is used instead of the H3PW. 12 O 40 Replace with K3PW 12 O 40 .
[0051] Example 5
[0052] It is basically the same as Example 3, except that the H3PW in step (4) is used instead of the H3PW. 12 O 40 Replace with NH4H2PW 12 O40 .
[0053] Comparative Example 1
[0054] The process is basically the same as in Example 3, except that no phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase and KEGIN-structured phosphotungsten heteropolyacid nanoclusters are added. Instead, the porous manganese-cerium composite oxide host phase obtained in step (1) of Example 3 is used as the composite photocatalytic material.
[0055] Comparative Example 2
[0056] The process is basically the same as in Example 3, except that the porous manganese-cerium composite oxide host phase and the manganese-based composite intermediate loaded with phosphorus / sulfur co-doped carbon-nitrogen quantum dots obtained in step (1) of Example 3 are used, but the kogerin structure phosphotungsten heteropolyacid nanoclusters are not introduced.
[0057] Comparative Example 3
[0058] The process is basically the same as in Example 3, except that the porous manganese-cerium composite oxide host phase and the supported Kieger structure phosphotungsten heteropolyacid nanoclusters obtained in step (1) of Example 3 are used, but the manganese-based composite intermediate of phosphorus / sulfur co-doped carbon-nitrogen material is not introduced.
[0059] Comparative Example 4
[0060] The process is basically the same as in Example 3, except that it is prepared using the porous manganese cerium composite oxide host phase, undoped g-C3N4 nanosheets, undoped carbon and nitrogen quantum dots, and KEGIN structure phosphotungsten heteropolyacid nanoclusters obtained in step (1) of Example 3.
[0061] The undoped g-C3N4 nanosheets were purchased from Suzhou Kaifa New Material Technology Co., Ltd., item number: BKMK513-01.
[0062] The undoped carbon and nitrogen quantum dots were purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0063] Comparative Example 5
[0064] The process is basically the same as in Example 1, except that the porous manganese-cerium composite oxide host phase in step (1) is replaced by commercially available porous manganese dioxide.
[0065] Test Example 1
[0066] Specific surface area and relative oxygen vacancy content were tested using the composite photocatalytic materials obtained in Examples 1-5 and Comparative Examples 1-5 for in-situ regeneration of manganese-based catalysts. Specific surface area was determined using the nitrogen adsorption-desorption method. The testing instrument was a fully automated specific surface area and pore size analyzer. Before testing, the samples were degassed under vacuum at 200℃ for 6 hours to remove adsorbed moisture and impurities from the sample surface. Subsequently, nitrogen adsorption-desorption tests were performed at liquid nitrogen temperature, and the specific surface area of the samples was calculated using the BET method. Each group of samples was tested four times, and the average value was taken. The results are shown in Table 1.
[0067] The relative content of surface oxygen vacancies was characterized using X-ray photoelectron spectroscopy (XPS). During testing, Al Kα was used as the excitation source, and the O 1s peaks on the sample surface were fitted using peak segmentation. The low binding energy peak corresponding to lattice oxygen was denoted as Oα, and the high binding energy peaks corresponding to defect oxygen and adsorbed oxygen related to oxygen vacancies were denoted as Oβ. The relative content of surface oxygen vacancies was characterized by the percentage of the Oβ peak area to the total O 1s peak area. Each sample was tested four times, and the average value was taken. The results are shown in Table 1.
[0068] Table 1. Results of specific surface area and relative content of surface oxygen vacancies.
[0069] Example 1 124.6 15.6 Example 2 135.3 18.1 Example 3 149.9 23.4 Example 4 145.7 21.3 Example 5 147.9 21.8 Comparative Example 1 86.6 8.7 Comparative Example 2 102.5 10.3 Comparative Example 3 95.6 11.5 Comparative Example 4 125.4 12.4 Comparative Example 5 68.7 7.6
[0070] Test Example 2
[0071] Catalytic efficiency, regeneration capacity, and post-regeneration catalytic efficiency tests of the catalyst before and after deactivation:
[0072] The composite photocatalytic materials obtained in Examples 1-5 and Comparative Examples 1-5 were used as the main catalysts to be tested. 0.20 g of each sample was weighed, pressed into tablets, pulverized and passed through a 40-60 mesh sieve, and packed into a fixed-bed quartz reactor. The catalyst bed was fixed with quartz wool on the top and bottom.
[0073] Catalytic efficiency was tested using the fixed-bed online evaluation method. The test conditions were: reaction temperature 120℃, inlet gas composition of a mixture of 500 ppm NO, 500 ppm NH3, 5 vol% O2, and the balance N2, and a space velocity of 30,000 h⁻¹. -1 A 420nm LED visible light source was used to irradiate the outer wall of the reactor, with a light intensity of 80mW / cm². After the reaction stabilized for 30 minutes, the outlet NO concentration was recorded, and the catalytic efficiency was calculated using the following formula: Catalytic efficiency (%) = (Inlet NO concentration - Outlet NO concentration) / Inlet NO concentration × 100%
[0074] After completing the pre-deactivation catalytic efficiency test, without removing the catalyst sample from the reactor, the atmosphere was directly switched to deactivation. A mixed gas containing 500 ppm NO, 500 ppm NH3, 100 ppm SO2, 5 vol% O2, 5 vol% H2O, and the balance N2 was introduced at 120°C with a space velocity of 30,000 h⁻¹. -1 The process was continuously treated for 8 hours to simulate the deactivation process of the composite photocatalyst material under sulfur- and water-containing conditions. After the deactivation treatment, the test atmosphere was switched back to that before deactivation, and the catalytic efficiency after deactivation was tested under the same light conditions.
[0075] Subsequently, in-situ regeneration was performed without removing the deactivated sample: first, the reactor was purged with N2 for 20 minutes to remove residual SO2, NH3, and NOx; then, under 420nm LED visible light irradiation, a regeneration gas containing 5 vol% O2, 3 vol% H2O, and the balance N2 was introduced at 120℃ for 2 hours to complete the in-situ regeneration. After regeneration, the initial test atmosphere was switched back, i.e., reaction temperature 120℃, inlet gas composition 500ppm NO, 500ppm NH3, 5 vol% O2, balance N2, and space velocity 30000 h⁻¹. -1 The catalytic efficiency after regeneration was tested under the same light conditions.
[0076] The regeneration capacity was calculated using the following formula: Regeneration capacity (%) = (catalytic efficiency after regeneration - catalytic efficiency after deactivation) / (catalytic efficiency before deactivation - catalytic efficiency after deactivation) × 100%. Each group of samples was tested 4 times, and the average value was taken. The results are shown in Table 2.
[0077] Table 2. Test results of catalytic efficiency and regeneration capacity of composite photocatalytic materials before and after deactivation.
[0078] Example 1 84.8 51.5 76.1 73.1 Example 2 87.8 54.7 80.9 79.9 Example 3 92.5 61.4 89.5 92.4 Example 4 90.7 58.1 86.2 87.8 Example 5 91.2 58.8 87.5 90.2 Comparative Example 1 61.8 34.9 44.2 33.3 Comparative Example 2 73.9 43.5 62.5 61.5 Comparative Example 3 71.8 40.7 57.0 53.7 Comparative Example 4 79.4 47.1 67.6 64.3 Comparative Example 5 59.1 33.5 40.4 29.0
[0079] As shown in Tables 1 and 2, the specific surface area, relative content of surface oxygen vacancies, catalytic efficiency before deactivation, catalytic efficiency after regeneration, and regeneration capacity of the composite photocatalytic materials obtained in Examples 1-5 of this invention are significantly better than those of the comparative examples. This indicates that there is a significant synergistic effect among the manganese-cerium composite oxide host phase, the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase, and the KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters. Among them, the indicators of Example 3 are the best. This is because the manganese-cerium composite oxide host phase is conducive to improving oxygen migration ability and stability of high-valence manganese species, the dual photosensitive phase can enhance visible light absorption and carrier separation efficiency, and the KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters further promote interfacial electron transfer and the formation of surface acidic sites, thereby synergistically improving the material performance.
[0080] The comparison between the various embodiments further shows that Embodiments 1 and 2, which each used only one phosphorus / sulfur co-doped carbon material as the photosensitive phase, had lower structural parameters and regeneration performance than Embodiment 3. This indicates that a single photosensitive phase has limited effect on promoting material interface regulation and photogenerated electron transport, while the synergistic effect of dual photosensitive phases is more beneficial for improving structural openness, the number of defect sites, and photocatalytic regeneration efficiency. Embodiments 4 and 5, which only changed the type of Kiegan-structured phosphotungsten heteropolyacid-based nanoclusters, had slightly lower overall performance than Embodiment 3, but were still significantly better than Embodiments 1 and 2. This indicates that different Kiegan-structured phosphotungsten heteropolyacid-based nanoclusters can enhance the acidity and electron transport ability of the material, among which the acidic H3PW... 12 O 40 The overall effect is better.
[0081] Compared to the examples, Comparative Example 1 only used a manganese-cerium composite oxide host phase, lacking a photosensitive phase and KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters. Its performance was significantly lower, indicating that a single host phase is insufficient to simultaneously achieve visible light response, deposit activation and decomposition, and regeneration recovery. Comparative Examples 2 and 3 lacked KEGIN-structured phosphotungsten heteropolyacid-based nanoclusters or phosphorus / sulfur co-doped carbon materials, respectively. Their performance was lower than that of Example 3, demonstrating that relying on a single functional component is insufficient to achieve optimal results. In Comparative Example 4, replacing the phosphorus / sulfur co-doped carbon material with undoped carbon material resulted in a decrease in the relative content of surface oxygen vacancies, catalytic efficiency, and regeneration capacity. This indicates that phosphorus and sulfur co-doping plays a crucial role in improving the electronic structure of carbon materials and enhancing carrier separation efficiency. In Comparative Example 5, replacing the manganese-cerium composite oxide host phase with commercially available porous manganese dioxide resulted in the lowest performance, indicating that cerium doping plays a key role in improving the oxygen vacancy content, oxygen migration capacity, and high-valence manganese species recovery capacity of the host phase.
Claims
1. A composite photocatalytic material for in-situ regeneration of manganese-based catalysts, characterized in that, The composite photocatalytic material used for in-situ regeneration of manganese-based catalysts includes a manganese-cerium composite oxide host phase, a phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase, and a KEGIN-structured phosphotungsten heteropolyacid nanocluster. The manganese-cerium composite oxide host phase is a porous structure enriched with oxygen vacancies. The phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase is loaded on the surface of the manganese-cerium composite oxide host phase. The KEGIN structure phosphotungsten heteropolyacid nanoclusters are fixed on the surface of the manganese-cerium composite oxide host phase and form an interface contact with the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase. The composite photocatalytic material used for in-situ regeneration of manganese-based catalysts can promote the removal of deposits on the surface of deactivated manganese-based catalysts and promote the recovery of high-valence active sites of manganese under visible light irradiation and oxygen-containing atmosphere.
2. The composite photocatalytic material for in-situ regeneration of manganese-based catalysts according to claim 1, characterized in that, The manganese-cerium composite oxide host phase accounts for 70-90 wt% of the total mass of the composite photocatalytic material, the phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase accounts for 3-15 wt%, and the KEGIN-structured phosphotungsten heteropolyacid nanoclusters account for 2-12 wt%.
3. The composite photocatalytic material for in-situ regeneration of manganese-based catalysts according to claim 1, characterized in that, The phosphorus / sulfur co-doped carbon-nitrogen photosensitive phase is one or both of phosphorus / sulfur co-doped carbon-nitrogen quantum dots and phosphorus / sulfur co-doped graphitic carbon nitride nanosheets; the average particle size of the carbon-nitrogen quantum dots is 2-10 nm, and the thickness of the graphitic carbon nitride nanosheets is 1-20 nm.
4. The composite photocatalytic material for in-situ regeneration of manganese-based catalysts according to any one of claims 1-3, characterized in that, The Kegerin-structured phosphotungsten heteropolyacid nanoclusters are H3PW 12 O 40 NH4H2PW 12 O 40 K3PW 12 O 40 One or more of them.
5. The composite photocatalytic material for in-situ regeneration of manganese-based catalysts according to claim 1, characterized in that, The composite photocatalytic material used for in-situ regeneration of manganese-based catalysts has a specific surface area of 50-250 m². 2 / g, with a relative content of 5-30% of surface oxygen vacancies.
6. A method for preparing a composite photocatalytic material for in-situ regeneration of manganese-based catalysts as described in any one of claims 1-5, characterized in that, Includes the following steps: (1) Manganese and cerium sources were used to prepare a manganese-cerium composite oxide precursor by hydrothermal method and then heat-treated to obtain a porous manganese-cerium composite oxide host phase; (2) Introduce a precursor containing P, S and N onto the surface of the main phase and form a phosphorus / sulfur co-doped carbon and nitrogen photosensitive phase by thermal polymerization or hydrothermal treatment; (3) Phosphotungstic acid or its ammonium salt or alkali metal salt is introduced into the surface of the main phase of the manganese cerium composite oxide or the surface of the composite intermediate loaded with phosphorus / sulfur co-doped carbon and nitrogen photosensitive phase and fixed to obtain the composite photocatalytic material for in-situ regeneration of manganese-based catalyst.
7. The preparation method according to claim 6, characterized in that, The manganese source in step (1) is one or more of manganese nitrate, manganese acetate, and manganese chloride, and the cerium source is one or more of cerium nitrate, cerium acetate, and cerium chloride; the heat treatment temperature is 300-500℃ and the time is 1-5h.
8. The preparation method according to claim 6, characterized in that, The precursor containing P, S, and N in step (2) includes one or more of melamine, urea, thiourea, trithiocyanate, ammonium dihydrogen phosphate, and phytic acid; the thermal polymerization temperature is 350-550℃ and the time is 0.5-4h; or phosphorus / sulfur co-doped carbon-nitrogen quantum dots are prepared by hydrothermal method at 160-220℃.
9. The preparation method according to any one of claims 6-8, characterized in that, The fixed processing temperature in step (3) is 120-300℃, and the time is 0.5-3h.
10. The use of the composite photocatalytic material according to any one of claims 1-6 in recyclable manganese-based composite photocatalytic materials.